REGIONAL INCLUSIVE GROWTH IN THE REBANA METROPOLITAN AREA: A SECTORAL AND REGIONAL ECONOMIC ANALYSIS PERSPECTIVE - Andis Destrian Irianto; Mega Tri Wulandari; Fauzan Isya Duri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study provides an original contribution by integrating multiple regional economic analysis tools to examine sectoral linkages and inclusive growth dynamics in the Rebana Metropolitan Area, a newly designated growth center in West Java. The research aims to identify base, prospective, and competitive sectors and to assess their implications for inclusive and balanced regional economic development. Using quantitative analysis of GRDP data from 2020–2023, the study applies Location Quotient, Dynamic Location Quotient, Klassen Typology, and shift-share analysis. The empirical results indicate that the manufacturing sector is simultaneously a base, prospective, and highly competitive sector, making it the main driver of economic growth in the Rebana Region. In contrast, other base sectors do not consistently show strong future prospects, while several supporting and service sectors demonstrate positive competitive dynamics, suggesting emerging economic diversification. These findings imply the need for an integrated development strategy that strengthens intersectoral and interregional linkages, upgrades socially important but less prospective sectors, and promotes a more equitable distribution of development benefits to support inclusive and sustainable economic transformation in West Java.